Formation features of microstructure, elemental and phase compositions of the C-Cr-Mn-V-Fe coatings under conditions of electron beam (EB) Surfacing in vacuum; Materials Physics and Mechanics; Vol. 52, iss. 1 - N. K. Nina Konstantinovna Galchenko (2024, 2024)
Заглавие с экрана